Literature as a Vehicle of Peaceful Counter-discourse: An Analysis of Native American Writings - Akhtar, Amer; Almas, Neelum (Journal of Peace, Development and Communication, 2021)
This article seeks to analyse key Native American literary works with a view to discussing the thematic concerns of this generally ignored tradition of literature. We discuss that the Native American literature serves as a peaceful means of producing and disseminating counter-discourse. The conquest--genocide for some--of the Native Americans is presented in all its horrific details but in a manner that engages and educates the reader. Writers like Alexie, Momaday, Silko, and Robe discuss not just the history of the abuse but also what it has led to and the forms it occurs in, in the present day. The article is significant in that it discusses a literature and a people systematically ignored by the mainstream and also in that it asserts that literature needs to be discussed as a player in the field of peace and communication.